Aedes spp. and Their Microbiota: A Review - Scolari, Francesca; Casiraghi, Maurizio; Bonizzoni, Mariangela (Frontiers in Microbiology, 2019)
Aedes spp. are a major public health concern due to their ability to be efficient vectors of dengue, Chikungunya, Zika and other arboviruses. With limited vaccines available and no effective therapeutic treatments against arboviruses, the control of Aedes spp. populations is currently the only strategy to prevent disease transmission. Host-associated microbes (i.e. microbiota) recently emerged as a promising field to be explored for novel environmentally-friendly vector control strategies. In particular, gut microbiota is revealing its impact on multiple aspects of Aedes spp. biology, including vector competence, thus being a promising target for manipulation. Here we describe the technological advances, which are currently expanding our understanding of microbiota composition, abundance, variability and function in the two main arboviral vectors, the mosquitoes Aedes aegypti and Aedes albopictus. Aedes spp. microbiota is described in light of its tight connections with the environment, with which mosquitoes interact during their various developmental stages. Unravelling the dynamic interactions among the ecology of the habitat, the mosquito and the microbiota have the potential to uncover novel physiological interdependencies and provide a novel perspective for mosquito control.